Israel's Security Networks : A Theoretical and Comparative Perspective / [electronic resource] - Sheffer, Gabriel; Barak, Oren (Cambridge : Cambridge University Press, 2013)
Since the establishment of the State of Israel in 1948, and particularly after the Israeli-Arab War of 1967, a highly informal but simultaneously potent security network has influenced Israel's domestic sphere. Composed of acting and former security personnel and their partners in the state's various civilian spheres, this security network has affected Israeli culture, politics, society, economy, public discourse and foreign relations. This book discusses this major sociopolitical phenomenon and its effects in a comparative and theoretical perspective. First, it defines Israel's security network in a broad theoretical and comparative perspective. Second, it explains how Israel's security network emerged and acquired a hegemonic position in the area of national security and foreign policy. Third, it describes the security network and identifies its members. Fourth, it discusses and explains the multitude of roles that Israel's security network has come to play both domestically and externally. Fifth, it discusses similar phenomena in other relevant cases. Finally, it presents general analytical and theoretical conclusions.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).